STRUCTURE AND CONTENT OF COMPETENCES ON THE BASIСS OF QUANTUM INFORMATICS OF PUPILS FROM LYCEUMS - Lehka, Liudmyla (Physical and Mathematical Education, 2021)
The results of the expert survey about identifying the components of competences on the basics of quantum informatics of pupils from lyceums are presented in the article. Formulation of the problem. The rapid development and promise of quantum technologies in the world are obvious prerequisites of the another transforming of the informatics education content in the Ukrainian general secondary education establishments, as well as clarification of the results of its mastery, there are the components of information and communication (digital) competence. In May 2021, The QTEdu consortium released the first version of the European Competence Framework for Quantum Technologies, components of which are the basis for identifying of the relevant competences for students, in particular full secondary education, as well as for the implementation and realization of educational and scientific projects in the quantum technologies. Materials and methods. To obtain the results of the study, an empirical method was used (a survey in the form of a semi-open questionnaire, where along with the answer options presented, could be expressed own meaningful comments-recommendations) and a statistical analysis of the results of the survey was done (range to identify the significance of the competencies components). Results. The conducted expert survey, which was attended mainly by teachers and lecturers, has provided answers and recommendations for the final identification of the content of competencies in quantum informatics of pupils from lyceums: competencies on the physical basics of quantum technologies; competencies on the mathematical foundations of quantum computer science; competencies on enabling technologies; competence in hardware of quantum computers and sensors; competence in quantum computing and modeling; competence in quantum sensors and metrology; competences in quantum communication; practical and soft skills. Conclusions. The determined structure and content of competencies on the basics of quantum computer science for pupils from lyceums were allowed to clarify the content of the relevant optional course.